The complete chloroplast genome sequence of Horsfieldia kingii (Myristicaceae) - Li, Xiao-Qin (Mitochondrial DNA B Resour, 2019)
Horsfieldia kingii is a member of Myristicaceae. The H. kingii chloroplast genome is found to be 155,655 bp in length and has a base composition of A (30.03%), G (19.52%), C (19.72%), and T (30.73%). The genome contained two short inverted repeat (IRa and IRb) regions (48,052 bp) which were separated by a large single copy (LSC) region (86,912 bp) and a small single copy (SSC) region (20,691 bp). The genome encodes 123 unique genes, including 85 protein-coding genes, 27 transfer RNA (tRNA) genes, and 8 ribosomal RNA (rRNA) genes. Further, complete chloroplast sequence of H. kingii was aligned together with other 2 species of Myristicaceae and other 5 basal angiosperms species which have reported the complete chloroplast sequence. This complete chloroplast genome will provide valuable information for the development of DNA markers for future species resource development and phylogenetic analysis of H. kingii.